DETERMINAN PENGELOLAAN KEUANGAN BADAN LAYANAN UMUM: DIMODERASI OLEH SISTEM PENGENDALIAN INTERNAL : DETERMINANTS OF PUBLIC SERVICE AGENCY FINANCIAL MANAGEMENT: MODERATED BY THE INTERNAL CONTROL SYSTEM - Fathul Bahri; Azlina, Nur; Nasir, Azwir (Universitas Riau, 2024)
Financial management is a key aspect of organizational success, including the Regional Public Service Agency (BLUD) which has autonomy in financial and operational management. This study aims to analyze the effect of Transparency, Accountability, Quality of Human Resources, and Accounting Information Systems on BLUD Puskesmas Financial Management with Internal Control System as a moderating variable. The study was conducted at BLUD Puskesmas in the coastal areas of Riau Province, namely Meranti Islands Regency, Bengkalis Regency, and Dumai City, using the Probability Sampling method with cluster sampling technique and involving 152 respondents from 38 puskesmas. Data were collected through questionnaires and analyzed using the SEM-PLS method. The results showed that Transparency, Accountability, Quality of Human Resources, and Accounting Information Systems had a significant effect on financial management. The Internal Control System is proven to moderate the effect of Transparency and Accountability on financial management, but does not moderate the relationship between the Quality of Human Resources and Accounting Information Systems on financial management. These findings are expected to be the basis for developing better BLUD financial management theory and practice in the future.